MEDIA STRATEGIES AND THEIR INFLUENCE IN COMMUNICATING INFORMATION ON FEMALE GENITAL MUTILATION: A CASE OF MERU COMMUNITY IN THARAKA DISTRICT - Kaunga, Sammy; Ndati, Dr. Ndeti (International Journal of Communication and Public Relation, 2017)
Purpose: To establish the influence of media strategies in communicating information about female genital mutilation effectively among the Meru community of Tharaka District. Methodology: The study adopted a descriptive Survey approach to research. Findings: The correlation analysis revealed that media ambassadors and local language were positive and statistically significant in influencing effective communication. The correlation analysis also revealed that sheng language and public participation were not statistically significant in influencing effective communication. Unique contribution to theory, practice and policy: The findings of this study will be important to various groups. To start with, the anti FGM campaigners will benefit from this study as they will identify the flaws and advantages of using media strategies to communicate information on FGM. Secondly, the media companies will be in a position to establish which media strategies are in effective communication of FGM. Thirdly, the administrators in Tharaka District will be in position to identify with the Meru community in their region since they will get first hand information from the people. Fourthly, this study will be important to other scholars and researchers and will form a reference point for anyone who will be investigating and would want some knowledge on this topic. This study will bring out scholarly gaps, which will require the attention of other researchers.